If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-18=-15-3(6t+5)
We simplify the equation to the form, which is simple to understand
-18=-15-3(6t+5)
Reorder the terms in parentheses
-18=-15+(-18t-15)
Remove unnecessary parentheses
-18=-15-18t-15
We move all terms containing t to the left and all other terms to the right.
+18t=-15-15+18
We simplify left and right side of the equation.
+18t=-12
We divide both sides of the equation by 018 to get t.
t=-0.66666666666667
| 0(5m)=5m | | -x+3+3x=-19 | | 3=(3+2x)-2(1+3x) | | x-44=90 | | 6-4(x-1)=3x+2(x+5) | | 15*44= | | 12x+6=13x-1 | | 11y+2y= | | -(-40)+m=65 | | 3(y-2)=6y+1-2(-6y-1) | | 9*57= | | 6x=3x+-2+28 | | 95=5(2-y) | | 3000/40-40x= | | 3a+5b=14 | | -5x+2=x+26 | | 2m+(3+4)=19 | | 224/32 | | 12*44= | | 90=b+45 | | -[7z-(15z+9)]=9+(7z+5) | | 9x=-(27/7) | | x+84=114+x | | f(x)=2240x-16x^2 | | 3(x-3)+2(3x+1)=11 | | 125*9*16= | | -4x-4=2-7x | | 4/5x=-1(3/5) | | 15+a=21 | | 6x+7-2x+4=49(-3x-5)-17 | | (x^2/3)-5=7 | | M+79=78 |